Effects of Nitrogen Application Rate Under Straw Incorporation on Photosynthesis, Productivity and Nitrogen Use Efficiency in Winter Wheat - Wang, Jinjin; Hussain, Sadam; Sun, Xu; Zhang, Peng; Javed, Talha; Dessoky, Eldessoky S.; Ren, Xiaolong; Chen, Xiaoli (Frontiers in Plant Science, 2022)
Developing a nitrogen fertilizer (N) reduction method under straw incorporation is essentially important for increasing wheat productivity in terms of improved fertilizer use efficiency and high yield in semiarid areas. A two-year field experiment, with five different nitrogen application rates control (without N application, N0), low N (75 kg ha-1, N75), medium N (150 kg ha-1, N150), high N (225 kg ha-1, N225) and excessive N (300 kg ha-1, N300), was conducted in 2018 and 2019 to quantify their impacts on the photosynthetic characteristics, nitrogen utilization (in term of N accumulation, distribution and transportation, and residual soil NO3--N) and productivity of winter wheat. There was a significant impact of N rates on photosynthetic traits, and N accumulation in different organs. As compared with the N300, N150 and N225 improved the photosynthetic characteristics, increased N accumulation in grains by 5.55 and 10.97 %, the N contribution proportion of that accumulated after anthesis by 67.90 and 115.56%, and reduced residual N by 62.50 and 46.48%, respectively, thereby effectively improved N absorption efficiency and N contribution rates. Grain yield remained slightly or unchanged among N treatments. Although N0 and N75 treatments reduced the nitrate-N leaching but caused a significant reduction of 18.13 and 28.37%, respectively in grain yield. From these results, we conclude that N application at 150 and 225 kg·ha-1 under straw incorporation was the most effective fertilization method in achieving the higher photosynthetic characteristics, improving NUE and grain yield. This study provides theoretical and practical guidance for wheat production techniques.